Associations between maternal clinical features and fetal outcomes in pregnancies of mothers with connective tissue diseases. Issue 2 (4th March 2019) - Ohyama, Ayako; Tsuboi, Hiroto; Noma, Hisashi; Terasaki, Mayu; Shimizu, Masaru; Toko, Hirofumi; Honda, Fumika; Yagishita, Mizuki; Takahashi, Hiroyuki; Asashima, Hiromitsu; Hagiwara, Shinya; Kondo, Yuya; et al.
Abstract: Objectives: The purpose of this study is to clarify associations between maternal clinical features and adverse pregnancy outcomes (APOs) in mothers with connective tissue diseases (CTDs). Methods: We retrospectively examined maternal clinical features including backgrounds, autoantibodies, CTD flare-ups, and therapies during pregnancies as well as fetal outcomes in 90 pregnancies (66 mothers) at our hospital from January 2006 to September 2016. Results: Underlying CTDs were SLE ( N  = 41), MCTD ( N  = 10), RA ( N  = 15), SS ( N  = 10), and others ( N  = 14). Anti-SS-A antibody was detected in 60.3%, lupus anticoagulant (LAC) was in 11.4%, and anti-cardiolipin-β2glycoprotein1 antibody was in 18.5%. Flare-ups of CTDs occurred in 20 pregnancies (22.2%). Corticosteroids (CS) was administered in 73 pregnancies, immunosuppressants in four, and biologics in one. Among the 85 pregnancies other than five early abortions within 12 weeks of gestational age, 33 cases had APOs while the remaining 52 cases were normal. Although disease duration, MCTD, high dose of CS, flare-ups of CTDs, and positive LAC significantly correlated with APOs by univariate analysis, only MCTD was a significant independent predictor for APOs by multivariate analysis. Conclusion: Disease duration, MCTD, high dose of CS, flare-ups of CTDs, and LAC might be possible predictive risk factors for APOs in pregnancies with CTDs. Of these, MCTD was a significant independent risk factor.